Incidence of deep vein thrombosis in lower limb injury following cast immobilisation - Zairuddin, Abdullah Zawawi (2008)
A cohort prospective study conducted in Hospital Universiti Sains Malaysia (HUSM). Objectives 1. To determine the incidence ofDVT following cast inunobilization of the lower limb. 2. To determine whether level of cast causes DVT. 3. To determine possible predisposing factors leading to DVT. Introduction Patient who had undergone lower limb immobilization have an increased risk for the development of deep vein thrombosis and subsequent pulmonary embolism, a life threatening situation. One of the known causes for the development of deep vein thrombosis is by recent cast immobilization of lower extremities. The purpose of this study is to determine the incidence of deep vein thrombosis following lower limb immobilization by cast and its predisposing factors. Methods A total of 40 patients participated in the study where they must be on cast for at least 6 weeks duration. The incidence of deep vein thrombosis was determined by colour Doppler ultrasound.Results From 40 patients assessed during the study period, deep vein thrombosis was identified in only 1 patient after 6 weeks of casting. This gave the incidence rate of only 2.5%. Conclusion The rate of deep vein thrombosis in our community following lower limb immobilization by cast is very low. Thus, we could conclude that cast application is still a safe mode of treatment in lower limb injury and it is not necessary to start anti thrombolytic agent for prophylaxis forDVT.